Analysis of the structure of patients visits to the city polyclinic - Z. Kh. Agamov (Исследования и практика в медицине)
Purpose. The deﬁ ni on of structure of visits to doctors in the city policlinic.Materials and methods. According to the results of doctors interviewing, a form for registra on of pa ents visits was designed. 2531 visits to the therapists, urologists and surgeons were registered.Results. The propor on of visits not related to the medical care was: therapists – 46%, surgeons – 23,4%, urologists –26,9%. The reasons for visits not related to the medical care were: for preferen al prescrip ons; the doctors opinion for medical and social examina on, for health resort card, for providing to other ins tu ons, cer ﬁ cates; for referral to take tests, research and obtaining their results, for consulta on, hospitaliza on in other ins tu ons.Conclusion. In the structure of visits to doctors of the city polyclinic, a high propor on of visits are not related to the medical care.